Hematological Effects Following Ingestion of Allium cepa (Onion), Allium sativum Garlic and Treatment with Iodine in Albino Wistar Rats - Uduak I., Aletan (Pakistan Journal of Nutrition, 2014)
This study was aimed at assessing the extent to which ingestion of Allium cepa (onion) Allium sativum (garlic) and treatment with iodine affect haematological parameters of albino Wistar rats. The effect on total hemoglobin, hematocrit (PCV%), red blood cells (RBC) and mean cell hemoglobin concentration (MCHC) were carried out. Oral administration of onion and garlic extract led to a dose dependent decrease in the total haemoglobin level of normal rats which was not statistically significant (p<0.05). Treatment with iodine led to a statistically significant (p<0.05) decrease in the total hemoglobin of the positive control group (treated with iodine only). Oral administration of onion and garlic extract to the normal rats led to a decrease in the hematocrit which was not statistically significant (p<0.05). Nonetheless, treatment with iodine led to a statistically significant (p<0.05) drop in the hematocrit of the iodine treated rats administered with high dose onion when compared to the control. In the normal rats, oral administration of high dose garlic and onion extracts led to a statistically significant (p<0.05) increase in the RBC when compared with the control group however the iodine treated groups recorded a drop which was statistically significant (p<0.05) in the low dose onion and garlic groups. From these results, it becomes imperative not just to consider the effects of these Alliums on the haematological parameters but to consider fortification with nutrients while embarking on the various forms of fortification with iodine. This is of particular importance mainly in areas where nutritional anemia is a concern.